Analysis of Acceptability and Potassium Contects of Red Bean Pudding (Phaseolus vulgaris L.) with the Addition of Roselle Extract (Hibicus Sabdariffa L.) as an Alternative Snack for Hypertension Patients: Analysis of Acceptability and Potassium Contects of Red Bean Pudding (Phaseolus vulgaris L.) with the Addition of Roselle Extract (Hibicus Sabdariffa L.) as an Alternative Snack for Hypertension Patients - Khoiria, Alfi Lailatul (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Pudding is a type of dessert that is loved by many people of all ages. The formulation of a snack that can be developed is making pudding made from high potassium foodstuffs, namely red beans which contain potassium of 1151 mg per 100 gr, and rosella flowers which contain potassium of 49.35 mg per 100 g which can be used as alternative snacks for people with hypertension. . The aim of this study was to determine the effect of adding rosella flower essence on the acceptability of the pudding and the potassium content in the selected formula based on the hedonic test. This study used a pure experimental research method with the addition of rosella flower essence, namely 15%, 20%, and 25%, which were then tested on 35 semi-trained panelists. Data were analyzed descriptively quantitatively with diagrams and statistics using the Kruskal Wallis and Mann Whitney tests (? = 0.05). The selected pudding formula is determined by looking at the results of the highest acceptability average value. Potassium content was tested in the laboratory using the Atomic Absorption Spectrophotometry (AAS) method. The results of the Kruskall-Wallis test showed that there was a significant effect on taste and aroma (? < 0.05), but there was no significant effect on color and texture (? > 0.05). The results of acceptability of pudding with the highest average level of preference were red bean pudding with the addition of 20% rosella flower essence. Test results for potassium content in red bean pudding with the addition of selected rosella flower essence in 100 gr are 21.64 mg, which can meet the contribution of 44% of the need for potassium in snacks